Cassio Dione e le guerre civili di età severiana - Schettino, María Teresa (Gerión. Revista de Historia Antigua, 2001)
This paper focuses on some features of Dio’s narrative of the civil wars in the Severian age, namely the references to the Republican personalities, first of all Sulla. This analysis leads to a reflection on the genesis of Dio’s History and the date of its composition